Educação financeira: uma proposta de abordagem nos anos finais do ensino fundamental - LOPES, Shirlane Bessa Ferreira (2022)
Financial Education has been gaining great social importance in recent years, research shows that the indebtedness and default rates are high, and consequently the financial indices of the Brazilian population are low according to the Financial Citizenship Reports of the Central Bank of Brazil, showing that great part of the citizens still does not have a healthy financial life, thus emphasizing the urgency of disseminating the issue in society. In this sense, the present work intends from the teacher training to collaborate with the insertion of financial education in schools, enabling the student to develop the ability to make good decisions in relation to finances. Therefore, the work was based on bibliographic research about Financial Education and its legal development, as well as the conceptual and pedagogical model. In addition, virtual workshops were offered to teachers of the public education network of Vale do Acará/PA and students of the Mathematics Course of the University Campus of Abaetetuba in order to promote understanding of the transversal relationship of financial education with the different areas of knowledge proposed. in the National Curricular Common Base (BNCC).